1997
DOI: 10.1093/infdis/175.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation of GB Virus C Infection in Hemophiliacs in Japan

Abstract: RNA of a putative non-A, -B, -C, -D, or -E hepatitis virus named GB virus C (GBV-C) was detected by reverse transcription-polymerase chain reaction with primers deduced from the 5' untranslated region in 15 (24%) of 63 men with hemophilia in Japan at a frequency higher (P < .001) than that in 2 (0.6%) of 337 controls. By phylogenetic analysis, GBV-C isolates from some patients were similar in sequence, indicating infection with closely related strains, and those from certain patients resembled sequences report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
1
15
0
3
Order By: Relevance
“…Several studies of GBV-C/HGV prevalence in HIV-infected patients have been published; a high frequency of GBV-C/HGV genome detection was also found: 10/55 (18.2%) in individuals with HIV-infection, but HIV risk groups weren't specified [Feucht et al, 1997b], 9/100 (9%) in intravenous drug users and homosexual men [Nü bling and Löwer, 1996], 8/33 (24%) in HIV-infected hemophiliacs [Kinoshita et al, 1997], 3/17 (17.6%) in HIVinfected pregnant women [Feucht et al, 1996], 2/20 (10%) in another series of HIV-seropositive hemophiliacs [Jarvis et al, 1996], and 11/41 (26.8%) in Japanese hemophilia patients with HIV coinfection [Toyoda et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies of GBV-C/HGV prevalence in HIV-infected patients have been published; a high frequency of GBV-C/HGV genome detection was also found: 10/55 (18.2%) in individuals with HIV-infection, but HIV risk groups weren't specified [Feucht et al, 1997b], 9/100 (9%) in intravenous drug users and homosexual men [Nü bling and Löwer, 1996], 8/33 (24%) in HIV-infected hemophiliacs [Kinoshita et al, 1997], 3/17 (17.6%) in HIVinfected pregnant women [Feucht et al, 1996], 2/20 (10%) in another series of HIV-seropositive hemophiliacs [Jarvis et al, 1996], and 11/41 (26.8%) in Japanese hemophilia patients with HIV coinfection [Toyoda et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it seemed that HIV by itself did not increase GBV-C/HGV prevalence. For instance, Stark et al [1996] did not find any association of GBV-C/HGV prevalence with HIV antibodies in intravenous drug users and homosexual men; 24% of hemophiliacs with HIV antibodies, vs. 23% without HIV antibodies, were GBV-C/ HGV-positive for Kinoshita et al [1997]; Jarvis et al [1996] found GBV-C/HGV RNA in 10% of HIV-infected hemophiliacs vs. 11/75 (14.7%) of HIV-negative hemophiliacs; GBV-C/HGV RNA status was not associated with HIV in 246 intravenous drug users (OR, 0.9 ; 95% CI; 0.4-2.0) [Thomas et al, 1997]; GBV-C/HGV RNA was detected in 11% and 8%, respectively, of HIVpositive and HIV-negative patients (81 hemophiliacs) [Goedert et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though HGV infection is common worldwide, the prevalence is high in Thailand (4.3%) [14], Vietnam (5.7%) [15], Germany (4.7%) [16], South Africa (10.4-12.9%) [10] and West Africa (14.2%) [17], but low in Japan (0.6-0.9%) [18][19][20], China (0.7-2.0%) [21][22][23] and the United States (0.8-1.7%) [5,17].…”
Section: Hgv Infection In the General Population And Blood Donorsmentioning
confidence: 99%
“…Determinadas populações de pacientes têm alta prevalência do GBV-C, a saber, portadores de insuficiência renal crônica em hemodiálise (ZHU et al, 2003;MASUKO et al, 1996;DE LAMBALLERIE;CHARREL;DUSSOL, 1996), hemofílicos (KINOSHITA et al, 1997) e usuários de drogas injetáveis (STARK;BIENZLE;. O presente estudo investiga a presença do RNA GBV-C no plasma de doadores de sangue saudáveis.…”
Section: Introductionunclassified